Wickerhamomyces sinyiensis f.a., sp. nov., a new ascomycetous yeast species in the Wickerhamomyces clade isolated in Taiwan. Issue 7 (22nd July 2022) - Chang, Chin-Feng; Hsu, I-Min; Liu, Chun-Hao; Lee, Ching-Fu
Abstract : This study describes Wickerhamomyces sinyiensis, a new anamorphic ascomycetous yeast species, four strains of which were isolated from soil and the fruiting body of a mushroom in Taiwan between 2006 and 2007. Analysis of the sequences of the large-subunit rRNA, small-subunit rRNA and elongation factor-1α identified this species as a member of the Wickerhamomyces clade. The yeast strains of W. sinyiensis exhibited a 0–3 nucleotide difference in the sequences of the D1/D2 domain of the large subunit rRNA when compared to one another and a 10 and 11 nucleotide difference when compared to Candida sp. BG99-11-14-10-4-1 and NRRL Y-7574, the closest undescribed species, respectively. The yeast strains differed by 77 and 78 nucleotides from W. orientali s and W. bispora, the close Wickerhamomyces species, respectively. The internal transcribed spacer sequences of the four isolates exhibited a divergence of 106–108 substitutions from the recognized species W. xylosivorus . No sexual reproduction was observed. The strains differed from those of related species in terms of their carbon and nitrogen assimilation patterns. Therefore, this study proposes W. sinyiensis f.a., sp. nov. to accommodate these four strains, with W. sinyiensis BCRC 23185 T (isotype CBS 11432 T ; MycoBank number MB563484) as the holotype.